Anthropogenic and lightning‐started fires are becoming larger and more frequent over a longer season length in the U.S.A. Issue 4 (20th January 2020) - Cattau, Megan E.; Wessman, Carol; Mahood, Adam; Balch, Jennifer K.
Abstract: Aim: Over the past several decades, wildfires have become larger, more frequent, and/or more severe in many areas. Simultaneously, anthropogenic ignitions are steadily growing. We have little understanding of how increasing anthropogenic ignitions are changing modern fire regimes. Location: Conterminous United States. Time period: 1984–2016. Major taxa studied: Vegetation. Methods: We aggregated fire radiative power (FRP)‐based fire intensity, event size, burned area, frequency, season length, and ignition type data from > 1.8 million government records and remote sensing data at a 50‐km resolution. We evaluated the relationship between fire physical characteristics and ignition type to determine if and how modern U.S.A. fire regimes are changing sensu stricto given increased anthropogenic ignitions, and how those patterns vary over space and time. Results: At a national scale, wildfires occur over longer fire seasons (17% increase) and have become larger (78%) and more frequent (12%), but not necessarily more intense. Further, human ignitions have increased 9% proportionally. The proportion of human ignitions has a negative relationship with fire size and FRP and a positive relationship with fire frequency and season length. Areas dominated by lightning ignitions experience fires that are 2.4 times more intense and 9.2 times larger. Areas dominated by human ignitions experience fires that are twice as frequent and have a fire season that is 2.4 times longer. The effect of human ignitions on fire characteristics varies regionally. Ecoregions in the eastern U.S.A. and in some parts of the coastal western U.S.A. have no areas dominated by lightning ignitions. For the remaining ecoregions, more intense and larger fires are associated with lightning ignitions, and longer season lengths are associated with human ignitions. Main conclusions: Increasing anthropogenic ignitions – in tandem with climate and land cover change – are contributing to a 'new normal' of fire activity across continental scales.